Beneficial Effects of Soybean-Derived Bioactive Peptides - Il-Sup Kim (International Journal of Molecular Sciences, 2021)
Peptides present in foods are involved in nutritional functions by supplying amino acids; sensory functions related to taste or solubility, emulsification, etc.; and bioregulatory functions in various physiological activities. In particular, peptides have a wide range of physiological functions, including as anticancer agents and in lowering blood pressure and serum cholesterol levels, enhancing immunity, and promoting calcium absorption. Soy protein can be partially hydrolyzed enzymatically to physiologically active soy (or soybean) peptides (SPs), which not only exert physiological functions but also help amino acid absorption in the body and reduce bitterness by hydrolyzing hydrophobic amino acids from the C- or N-terminus of soy proteins. They also possess significant gel-forming, emulsifying, and foaming abilities. SPs are expected to be able to prevent and treat atherosclerosis by inhibiting the reabsorption of bile acids in the digestive system, thereby reducing blood cholesterol, low-density lipoprotein, and fat levels. In addition, soy contains blood pressure-lowering peptides that inhibit angiotensin-I converting enzyme activity and antithrombotic peptides that inhibit platelet aggregation, as well as anticancer, antioxidative, antimicrobial, immunoregulatory, opiate-like, hypocholesterolemic, and antihypertensive activities. In animal models, neuroprotective and cognitive capacity as well as cardiovascular activity have been reported. SPs also inhibit chronic kidney disease and tumor cell growth by regulating the expression of genes associated with apoptosis, inflammation, cell cycle arrest, invasion, and metastasis. Recently, various functions of soybeans, including their physiologically active functions, have been applied to health-oriented foods, functional foods, pharmaceuticals, and cosmetics. This review introduces some current results on the role of bioactive peptides found in soybeans related to health functions.